Mircea Eliade and the Fundamental Structures of Religious Life - Vernoff, Charles E (Journal of Dharma, 1986)
Within the past generation, the academic study of religion has begun to move toward crystallization of a differentiated and formalized academic discipline—a religiologie by any other name, although current practitioners would shrink from the boldness of the term. The study of religion has yet to progress to confident avowal of its logos such as Auguste Comte provided for sociologie in his 1837 christening of that modern discipline. Advance toward such a declaration of autonomy nonetheless gathers momentum, prodded especially by the emergence of departments of religious studies within secular American universities during the past two decades. I No scholar has been more instrumental in this advance than Mircea Eliade, just retired from a quarter century of service at the University of Chicago. Eliade, his colleagues and his students have sought to establish the "history of religions" as nothing less than an autonomous discipline endowed with its own methods and exhibiting its own integrity; and indeed, at least within the English-speaking world, the term now enjoys a certain indelible association with the Chicago school.